A Gel Pad Designed to Measure Muscle Volume Using Freehand 3‐Dimensional Ultrasonography. (9th September 2020) - Thomare, Julien; Lacourpaille, Lilian; McNair, Peter J.; Crouzier, Marion; Ellis, Richard; Nordez, Antoine
Abstract : We developed an innovative gel pad that covers the entire lower leg to remove artifacts due to the pressure of the transducer in freehand 3‐dimensional ultrasonography. In comparison to the reference method in water, this study showed that this new method was valid (bias, 3.4 mL; limit of agreement, 7.7 mL for a volume of ≈220 mL) and reliable (coefficient of variation, <1.1%) for the measurement of gastrocnemius medialis muscle volume. Considering that it is easier to use than the water tank technique, it has much promise for volumetric measurement of many muscles.